2018
DOI: 10.1016/j.jpedsurg.2018.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gastroschisis: A population-based study in California from 1995 to 2012

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 18 publications
6
71
0
2
Order By: Relevance
“…The overall prevalence estimates presented in this data brief for both gastroschisis and omphalocele are consistent with those previously reported in the literature (Mai et al, 2015;Springett et al, 2014;St Louis et al, 2017;Vo & Langlois, 2015;Vu et al, 2008). Variations in prevalence by maternal race/ethnicity, maternal age at delivery, maternal prepregnancy BMI, infant sex, and infant birth weight also largely reflect previously reported estimates (Anderson et al, 2018;Kirby, 2017;Kirby et al, 2013). Our results support the findings of Marshall et al (2015), who reported an increase in omphalocele in infants of older mothers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The overall prevalence estimates presented in this data brief for both gastroschisis and omphalocele are consistent with those previously reported in the literature (Mai et al, 2015;Springett et al, 2014;St Louis et al, 2017;Vo & Langlois, 2015;Vu et al, 2008). Variations in prevalence by maternal race/ethnicity, maternal age at delivery, maternal prepregnancy BMI, infant sex, and infant birth weight also largely reflect previously reported estimates (Anderson et al, 2018;Kirby, 2017;Kirby et al, 2013). Our results support the findings of Marshall et al (2015), who reported an increase in omphalocele in infants of older mothers.…”
Section: Discussionsupporting
confidence: 91%
“…Omphalocele prevalence estimates are roughly one-half those of gastroschisis, but the omphalocele prevalence may be underestimated due to the higher proportion of fetal deaths and terminations of omphalocele cases compared to gastroschisis (Akhtar et al, 2012;Brantberg et al, 2004;Kuleva et al, 2012;Perry et al, 2017;Springett et al, 2014). In addition, infants with omphalocele are more likely to be early preterm deliveries and have very low birth weights compared to infants with gastroschisis (Anderson et al, 2018;Bugge et al, 2017;Feldkamp et al, 2016;Marshall et al, 2015). Despite the increase in prevalence of gastroschisis that has been well-documented in the literature, it is clear that omphalocele also presents a large burden for families and the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Gastroschisis occurs in 2.1 to 5.3 per 10,000 live births. 2,[6][7][8] For reasons unknown, the worldwide birth prevalence of gastroschisis has increased dramatically over the last decades, but these studies have lacked the total prevalence. 2,7,8 The most consistent risk factor for gastroschisis is young maternal age, but interestingly the incidence is increasing in all age groups, not only in younger women.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroschisis is a common congenital defect [1]. The incidence of gastroschisis has increased three-fold over the last two decades in some regions [2]. While infants born with gastroschisis usually undergo abdominal closure within several days of birth, their mean hospital stay in the intensive care unit is greater than 30 days.…”
mentioning
confidence: 99%